Meta-analysis of molecular imaging of translocator protein in major depression - Eggerstorfer, Benjamin; Kim, Jong-Hoon; Cumming, Paul; Lanzenberger, Rupert; Gryglewski, Gregor (Frontiers in Molecular Neuroscience, 2022)
Molecular neuroimaging studies provide mounting evidence that neuroinflammation plays a contributory role in the pathogenesis of major depressive disorder (MDD). This has been the focus of a number of positron emission tomography (PET) studies of the 17-kDa translocator protein (TSPO), which is expressed by microglia and serves as a marker of neuroinflammation. In this meta-analysis, we compiled and analyzed all available molecular imaging studies comparing cerebral TSPO binding in MDD patients with healthy controls. Our systematic literature search yielded eight PET studies encompassing 238 MDD patients and 164 healthy subjects. The meta-analysis revealed relatively increased TSPO binding in several cortical regions (anterior cingulate cortex: Hedges’ g = 0.6, 95% CI: 0.36, 0.84; hippocampus: g = 0.54, 95% CI: 0.26, 0.81; insula: g = 0.43, 95% CI: 0.17, 0.69; prefrontal cortex: g = 0.36, 95% CI: 0.14, 0.59; temporal cortex: g = 0.39, 95% CI: –0.04, 0.81). While the high range of effect size in the temporal cortex might reflect group-differences in body mass index (BMI), exploratory analyses failed to reveal any relationship between elevated TSPO availability in the other four brain regions and depression severity, age, BMI, radioligand, or the binding endpoint used, or with treatment status at the time of scanning. Taken together, this meta-analysis indicates a widespread ∼18% increase of TSPO availability in the brain of MDD patients, with effect sizes comparable to those in earlier molecular imaging studies of serotonin transporter availability and monoamine oxidase A binding.